O TEXTO E O LEITOR EM MACHADO DE ASSIS:INTERSECÇÕES TEÓRICAS COM O CÍRCULO DE MIKHAIL BAKHTIN - Gomes, Izabele Caroline Rodrigues (2016)
This dissertation approaches Dom Casmurro and Memorial de Aires, Machado de Assis’ novels, aiming to set the reader’s role in the dialogical process triggered by the narratives, each one by its own way. For this, we have used some theoretical notions from Mikhail Bakhtin, like dialogism and plurilingualism, conceptions developed mainly, but not exclusively, in the texts from Questions of Literature and Aesthetics: Theory of the Novel (2010) and Aesthetics of Verbal Creation (2010). In this research, the reader’s figuration can be theorized as part of an interaction process with the novel’s narrator, the text itself and with the authorial figure. Thus, we have linked the Bakhtin’s concepts with Umberto Eco’s propositions, especially the idea of Model Reader, Empirical Reader, Model Author and Empirical Author, considering that this association can help us to analyze the two chosen novels. Machado de Assis starts a process of figuration of an active reader to his texts, leading a new reading procedure and initializing a route to train the ideal reader to understand the meanings that literature texts can create. Because of this, we have dedicated some analysis to the digressions, parodies, irony and metalinguistic effects from the novels studied.